Feeding broiler chicks diets containing keto- and hydroxy-acids: performance and carcass weight. (6th March 2019) - Adrizal, A; Patterson, P H; Angel, C R; Markant, A
ABSTRACT: This study evaluated reduced dietary CP and supplementing amino acid analogs to sustain growth and carcass weight in 0- to 21-day-old Cobb × Avian-48 male broiler chicks. A total of 6 diets with 3 levels of CP (22.5, 19.5, and 16.5%) and 2 sources of AA analogs, either synthetic amino acids (SA) or keto-/hydroxy-acids (KA), were assigned randomly to 36 cages (8 chicks/cage) in a 3 × 2 factorial design. For SA diets, DL-Met, DL-Met + L-Ile, and D-Met + L-Ile + L-Val were used to supplement 22.5, 19.5, and 16.5% CP diets, respectively, and for corresponding KA diets, DL-Met was replaced with methionine hydroxy analog (MHA), L-Ile was replaced with keto-Ile, and L-Val was replaced with keto-Val. Water and all isocaloric diets (3, 050 kcal ME/kg) were given ad libitum. Lowering dietary CP to 16.5% reduced BW at 7, 14, and 21 D ( P ≤ 0.0001) and feed intake at 8 to 14, 15 to 21, and 0 to 21 D ( P ≤ 0.001). Body weight gain (BWG) was reduced and feed-to-gain ratio (FGR) was increased ( P ≤ 0.003 to 0.0001) at all times for chicks fed 16.5% CP; however, chicks fed 22.5 and 19.5% CP had comparable performance. Differences in 0 to 7 D BWG (SA, 122.9 vs. KA, 113.9 g/bird; P ≤ 0.04), a 0 to 21 D FGR cumulative effect (1.45 vs. 1.51; P ≤ 0.02), and a 15 to 21 D ( P ≤ 0.04) and 0 to 21 D ( P ≤ 0.05) CP × AA interaction were also observed. Greater liver weight among 16.5 vs. 19.5 or 22.5% CP fed chicks was found at 14 and 21 D ( P ≤ 0.0001 and P = 0.06, respectively). Lower dietary CP reduced spleen weight on day 21 birds ( P ≤ 0.0005) with lighter spleens among 16.5 and 19.5% vs. the 22.5% CP fed group (0.090, 0.095, 0.119 g/100 g BW, respectively). Breast weight at 21 D was significantly less for 16.5 vs. 22.5% CP fed chicks. Fat pad weight on day 21 was heaviest among 16.5% chicks ( P ≤ 0.0004). Overall, lowering dietary CP to 16.5% had a negative effect, but keto-acid supplementation supported 0 to 21 D broiler growth compared to SA; however, transamination efficiency of KA may be lower for 0 to 7D old chicks compared to older birds.